KOMPOSISI DAN STRUKTUR VEGETASI PADA KAWASAN CAGAR ALAM GUNUNG TINOMBALA KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG - Hapshari, Novita; Umar, Husain; Ningsih, Sri (Jurnal Warta Rimba, 2015)
The research aimed to study the composition and structure of vegetation in Gunung Tinombala Nature Reserve area. The research was conducted from June through August 2013. This study uses line plots sampling method. There were three transects/lines with 20 m spacing between lines. Twenty measurement plots were made in each line. Hence vegetation date were analysed to determine the density, frequency, dominant, Importance Value Index and the Diversity Index of Shannon-Wienner. The results showed that the highest Importance Value Index (IVI) at tree and sapling level of vegetation were Eugenia sp.with value (23,38%) and (43,39%,) respectively. At pole level, the highest (IVI) was Caryota sp (35,08%). The highest (IVI) at seedling level was Horsfieldia costulata (11,69%). Furthermore, the stand structure founded in this area consisting of five stratums. First, stratum A was dominated by Eugenia sp, consisting of 35 plant species with density value was 14 individual plants ha -1 . second, Stratum B was domited Artocarpusteysmani, consisting of 35 plants species with density value was 11 individual plants ha -1. Third, Stratum C was dominated by Caryota sp, consisting of 30 plants species with density value was 50 individual plants ha -1 . Fourth, Stratum D was dominated by Eugenia sp, consisting of 22 plants species with density value was 180 individual plants ha -1. Fifth, Stratum E was dominated by Horsfieldiacostulata, consisting of 26 plants species with density value was 875 individual plants ha -1. Keywords : Species Composition, Vegetation Structure, Gunung Tinombala Nature Reserve, Importance Value Index